Adopsi Inovasi Fintech Berbasis Syariah di Indonesia: Studi Kasus Paylater Platform e-Commerce - Rico Elhando Badri; Soraya Asnusa; Edi Pranyoto; Susanti Susanti; Arif Gunawan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
Technology and automation have become an important part of the global financial services market. Fintech is dramatically changing the way consumers conduct financial transactions. Simply put, it is a paylater service that allows consumers to buy products in installments over a certain period on an e-commerce platform for various needs. Currently, in Indonesia, several fintech companies provide pay-later services. Its implementation appears in many applications, ranging from digital wallets, and ticket bookings, to the most popular on e-commerce platforms and/or online marketplaces. Each provider has different specifications and coverage. The differentiating variables include loan value limits, interest, tenor, loan terms, coverage area, and integration into third-party services. The purpose of this study is to propose an expanded model of the technology acceptance model (TAM) in the use of financial technology (Fintech) in paylater services, in particular, to study and explore the role of image and religiosity in TAM, as well as provide policy recommendations for authorized agencies and providers. services in Indonesia regarding several important factors that need to be considered so that Indonesian Muslims are willing to use Fintech. The sample in this study is a Muslim population aged at least 18 years who use Fintech pay-later to make payment transactions on e-commerce in Bandar Lampung. Testing the data using SEM PLS. The results showed that Islamic Religiosity and Image were able to increase the Attitude toward using fintech payment pay-later through Perceived Ease of Use as a mediating variable, but Islamic Religiosity and Image reduced the Attitude toward using fintech pay-later through Perceived Usefulness as a mediating variable.